2017
DOI: 10.1155/2017/1847428
|View full text |Cite
|
Sign up to set email alerts
|

Liver Metastases in Pancreatic Acinar Cell Carcinoma Treated with Selective Internal Radiation Therapy with Y-90 Resin Microspheres

Abstract: Background Pancreatic acinar cell carcinoma (PACC) is a rare tumor. Surgical resection is the treatment of choice when feasible, but there are no clear recommendations for patients with advanced disease. Liver-directed therapy with Y-90 selective internal radiation therapy (SIRT) has been used to treat hepatic metastases from pancreatic tumors. We describe a case of PACC liver metastases treated with SIRT. Case Report 59-year-old man was admitted with an infiltrative, solid lesion in pancreatic tail diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…With the development of glass and resin Y90 microspheres in the 1990s, several studies demonstrated its potential role for advanced-stage hepatocellular carcinoma [16]. Nowadays, its applications have evolved for several types of malignancies and for different situations in the treatment pathway for patients with cancer, not more restricted to the salvage setting for patients with chemorefractory disease [11,12,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of glass and resin Y90 microspheres in the 1990s, several studies demonstrated its potential role for advanced-stage hepatocellular carcinoma [16]. Nowadays, its applications have evolved for several types of malignancies and for different situations in the treatment pathway for patients with cancer, not more restricted to the salvage setting for patients with chemorefractory disease [11,12,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…This locoregional therapy was used from palliative care to neoadjuvant treatment in the treatment of several types of liver metastatic disease with encouraging outcomes [10][11][12]. Herein, we present a first-of-its-kind case where SIRT was successfully used in combination with other pre-established treatment options for metastatic upper urinary tract urothelial carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…We chose resection of the liver metastases for two reasons. First, liver metastases are often multiple in PACC [ 19 ]; however, in this case, it was solitary, slow growing, and relatively small even 24 months after the primary pancreatectomy. Second, additional chemotherapy was not favorable for this patient due to the severe side effects of the previous treatment with S-1.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely do patients with ACC are diagnose with lung, cervical lymph nodes, and ovary metastases. Metastatic illness is typically detected in regional lymph nodes and the liver[ 69 ]. Patients presenting as their first disease symptom with distant metastases are infrequent.…”
Section: Prognosis Factors Of Prediction Spread and Metastasesmentioning
confidence: 99%